2019
DOI: 10.1037/stl0000152
|View full text |Cite
|
Sign up to set email alerts
|

The pedagogical power of storytelling.

Abstract: Stories, as a means of teaching, have been a part of society since the beginning of human communication. The power of storytelling as pedagogy, however, may have been undervalued by educators. In this teacher-ready theory review, we present the connection between teaching and storytelling, highlight a variety of storytelling approaches, summarize why storytelling works as a pedagogical device, and conclude with suggestions and recommendations for implementing storytelling as a pedagogical approach. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 22 publications
0
32
1
Order By: Relevance
“…During the workshops, participants were provided with knowledge in terms of health benefits of regular PA, parenting tips, and principles of SDT through a story-telling approach. Since these topics may involve theoretical concepts that might be complex to children and parents, we used story-telling to facilitate understanding and improve memorability of key principles [ 33 , 34 ]. Apart from increasing participants’ knowledge, the workshops were designed with a goal of raising the importance of basic need satisfaction, and how parents can be more need supportive, and less controlling.…”
Section: Methodsmentioning
confidence: 99%
“…During the workshops, participants were provided with knowledge in terms of health benefits of regular PA, parenting tips, and principles of SDT through a story-telling approach. Since these topics may involve theoretical concepts that might be complex to children and parents, we used story-telling to facilitate understanding and improve memorability of key principles [ 33 , 34 ]. Apart from increasing participants’ knowledge, the workshops were designed with a goal of raising the importance of basic need satisfaction, and how parents can be more need supportive, and less controlling.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered one of the oldest forms of teaching and has allowed thousands of generations to exchange knowledge and values as well as learn from past experiences. 8 Storytelling , allows individuals to make sense of the complex world and construct their own meaning via learning from distal events, others' stories, and past experiences. 8,9 Previous studies have demonstrated that such effects of storytelling can be applied to students' learning and engagement outcomes.…”
Section: Rationale For Novel Application Of Tool/methods or Curricular Approachmentioning
confidence: 99%
“…8 Storytelling , allows individuals to make sense of the complex world and construct their own meaning via learning from distal events, others' stories, and past experiences. 8,9 Previous studies have demonstrated that such effects of storytelling can be applied to students' learning and engagement outcomes. In the context of teaching, storytelling has been considered a foundational approach that facilitates the personal relevance to the knowledge being taught, provides an easy way of comprehension when the information is transmitted in a narrative manner, and creates a more personal connection between the teacher and learners.…”
Section: Rationale For Novel Application Of Tool/methods or Curricular Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Stories differ from memories in that the content of stories does not necessarily originate from an individual's own experience. Empirical research exploring stories is voluminous and wellestablished, but has focused primarily on identifying features of stories, context, and cognitive processing that influence retention and emotional and behavioral impacts (Habermas and Diel, 2010;Dunlop et al, 2011;McGinty et al, 2013;Berger et al, 2019;Landrum et al, 2019). Not yet adequately explored is the enduring or cumulative influence of emotional stories, especially those that convey personal meaning.…”
Section: Introductionmentioning
confidence: 99%